Sakha Language in a Northern Industrial Monotown: Linguistic Distribution in Speech Repertoire of Sakha People - I. A. Danilov (Научный диалог, 2024)
This study explores the functioning of the Yakut language in the conditions of the northern industrial monotown Mirny (Republic of Sakha (Yakutia)). The study identifies the features of linguistic distribution in the speech repertoire of ethnic Sakha based on data from a sociolinguistic survey and interviews (n=279). Descriptive statistical methods and content analysis are employed. The results reveal an asymmetric nature of Yakut-Russian bilingualism with Russian language predominance in public communication. While Sakha individuals exhibit a high level of language competence in the Yakut language, its application is limited. In familial and friendly communication, the Yakut language maintains significant positions; however, its demand is minimal in the professional-business sphere, especially in industry. Among individuals with higher education, the percentage of Russian speakers at work reaches 68.34% compared to 55.77% among those with only secondary vocational education. Russian language dominates in management, service sectors, and law enforcement (75—100%). Only in fields such as healthcare, education, and culture does the Yakut language maintain strong positions. The native language is primarily perceived by Sakha as a symbolic marker of identity, yielding to Russian in social prestige and communicative power. The vitality prospects of the Yakut language in the city are assessed ambiguously and are linked to the effectiveness of language policy in key institutional contexts (education, media, government).